2011
DOI: 10.1001/jama.2011.746
|View full text |Cite
|
Sign up to set email alerts
|

KIT as a Therapeutic Target in Metastatic Melanoma

Abstract: Context Some melanomas arising from acral, mucosal, and chronically sun-damaged sites harbor activating mutations and amplification of the type III transmembrane receptor tyrosine kinase KIT. We explored the effects of KIT inhibition using imatinib mesylate in this molecular subset of disease. Objective To assess clinical effects of imatinib mesylate in patients with melanoma harboring KIT alterations. Design, Setting, and Patients A single-group, open-label, phase 2 trial at 1 community and 5 academic onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
529
1
22

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 782 publications
(569 citation statements)
references
References 40 publications
17
529
1
22
Order By: Relevance
“…Patients with melanomas harboring KIT mutations have a high probability of responding to nilotinib but usually with short duration of response compared with KIT-mutant GIST. Nilotinib compares similarly with previous trials with imatinib in terms of response rate and median PFS in melanoma [15,16]; however, the data do not allow the conclusion that the exon 17 (I817L) mutation or other mutations should preferably be treated with nilotinib. Single-mutant exon 17 mutations may respond to imatinib, and no preclinical evidence shows that these mutants are really resistant.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Patients with melanomas harboring KIT mutations have a high probability of responding to nilotinib but usually with short duration of response compared with KIT-mutant GIST. Nilotinib compares similarly with previous trials with imatinib in terms of response rate and median PFS in melanoma [15,16]; however, the data do not allow the conclusion that the exon 17 (I817L) mutation or other mutations should preferably be treated with nilotinib. Single-mutant exon 17 mutations may respond to imatinib, and no preclinical evidence shows that these mutants are really resistant.…”
Section: Resultsmentioning
confidence: 81%
“…Of the 2 patients with exon 11 V559A mutation, 1 showed partial response for 38 weeks and 1 showed stable disease for 16 weeks with nilotinib.V559A and N822I double KIT mutant melanoma has been shown to have some degree of response to imatinib [25]; therefore, our phase II trial demonstrated that nilotinib can induce durable responses in V559A KIT-mutated melanoma. Currently, four primary double KIT mutations in melanoma have been identified in the literature: N566D (exon 11)/K642E (exon 13) [13], N463S (exon 9)/N655S (exon 13) [15], K642E (exon 13)/ N822I (exon 17) [26], and V559A (exon 11)/N822I (exon 17) [25]. In our patient cohort, 1 patient had V560D (exon11)/ V654A(exon13) ( Table 3) and had stable disease for .42weeks on nilotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond BRAF, data from phase II trials indicate a possibility of clinical responsiveness to KIT inhibitors in the KIT-mutant melanoma population [33][34][35] . Otherwise, testing for NRAS or NF1 mutations is largely a matter of identifying patients who might be candidates for clinical trials.…”
Section: Genetic and Immune Landscape Of Melanomamentioning
confidence: 99%
“…24 Although infrequent, c-KIT mutations can be found in acral and mucosal melanomas; in several case reports, a rapid, but transient response was achieved with imatinib mesylate, a small molecule inhibitor of KIT and other tyrosine kinases. 25,26 These observations were confirmed in subsequent prospective, non-comparative phase 2 studies, in which imatinib resulted in response rates of approximately 20%, despite relatively short PFS intervals ranging from 2.8 to 3.7 months. 27,28 Taken together, although the benefit of targeted approaches in patients with melanoma harboring non-BRAF mutations has been limited, these results serve as a proof of concept for future molecularlydriven treatment strategies.…”
Section: Introductionmentioning
confidence: 66%